An exploratory study of the relationship between COVID-19 pandemic and volume of cryptocurrency investors in Eastern Visayas - Alfabete, Nicole Rose Liberty P.; Bucu, Angela Milvie N.; Mate, Kyla Jenn J.; Dacuyan, Flordeliz B. (2022)
This study examined the relationship between the COVID-19 pandemic and the volume of cryptocurrency investors in Eastern Visayas. The main objective is to determine how the COVID-19 pandemic economically affected the volume of cryptocurrency investors in the region. It delves into the factors that influence investors in investing during the pandemic, the volume of investors before and during the four waves of COVID-19 with regards to the identified factors, and the dangers perceived in investing in cryptocurrency amid the pandemic. A sequential mixed-method approach was adopted where data collection was done in a two-phased process, carried out through online communication platforms. The first phase commenced with an in-depth interview of ten cryptocurrency investors from the different provinces. Subsequently, a survey was conducted among 96 randomly selected crypto-investors across the region. With the use of Binary Logistic Regression, results show that only financial capacity is a significant predictor since it has a p-value of 0.043, which is less that 5%. This means that investors who have high financial capacity are less likely to invest in cryptocurrency during the pandemic. Findings also show a significant increase in the volume of crypto-investors in Eastern Visayas before and during the four waves of COVID-19 with the aid of McNemar's test. It presents a clear growth in the volume of investors as each wave passes. In terms of the dangers perceived, results present that scammers, volatility of the market, security of assets, the possibility of rug pull, inadequate knowledge in trading, suspicious source of NFT games, data privacy, ransomware, and untrusted brokers have frequency percentages higher than 60% which means to say that all the aforementioned risks are known and acknowledged by most crypto-investors in Eastern Visayas.
Undergraduate thesis (Bachelor of Science in Accountancy) -- University of the Philippines, Tacloban.